The N-terminal module of HPV16 E7 is an intrinsically disordered domain that confers conformational and recognition plasticity to the oncoprotein - Garcia Alai, Maria M. (2007)
The HPV16 E7 oncoprotein is an extended dimer, with a stable and cooperative fold, but that displays properties of "natively unfolded" proteins. Two regions of conserved sequence are found in E7 proteins, where the N-terminus (1-40) includes the retinoblastoma tumor suppressor binding and casein kinase II phosphorylation sites. A fragment containing the highly acidic N-terminal half shows an apparently disordered conformation by far-UV-circular dichroism (CD) at neutral pH, and its hydrodynamic radius is much larger than a neutral peptide of the same length. Trifluoroethanol and micellar concentrations of sodium dodecyl sulfate stabilize a much more helical structure at pH 4.0 than at pH 7.5, while submicellar concentrations of the detergent yield a beta-strand. The shape, pH, and temperature dependence of the CD spectrum at pH 7.5 are indicative of a poly proline type II structure. This structure is stabilized by phosphorylation, which would translate into increased transforming activity in the cell. Thus, the intrinsically disordered properties of the N-terminal module of E7 are responsible for the structural plasticity of the oncoprotein. Although the domain is not a compact and cooperatively folded unit, it is a bona fide functional domain, evolved to maintain a dynamic but extended structure in the cell. These properties allow adaptation to a variety of protein targets and expose the PEST degradation sequence that regulates its turnover in the cell, a modification of which leads to the accumulation of E7 species with consequences in the transformation process